Cyberspace Sebagai Ruang Publik Baru: Analisis Naratif Opini Publik Pada Isu Larangan ThrifTing Di Media Sosial Twitter - S, Nurul Fadhillah (Jurnal Ilmu Komunikasi Pattimura, 2023)
Cyberspace as the new public spheres, create people who are put into a situation where they can have an opinion, something that is difficult to realize if reform does not occur. One example of cyberspace is the emergence of social media which not only influences people's lives, but is also able to provide new ways of channeling aspirations.. There is the issue of prohibition of thrifting which is discussed by the public on social media and generates quite high attention from the community as actors and thrift users. This study analyzes narratively 10 screenshots of public opinion popping up on Twitter when searches are directed at two hashtags, #thrifting and #thriftingdilarang. As a result, public opinion circulating on Twitter is dominated by disappointment with this new rule. Comparisons were made publicly on flexing family officials, at the same time questioning the work of several parties and the fate of the people who work in the world of thrift shops like this. Keywords: cyberspace, public sphere, public opinion, thrifting, Twitter.